INSTRUCTIONAL LEADERSHIP: THE EFFECT OF TEACHING SELF-EFFICACY - Suryana, Asep; Ma’mun, Muflih (EARR (Educational Administration Research and Review), 2019)
The principal as leader who has the role to support and facilitate the needs of teachers in teaching activities. When the principal's role can be carried out properly, it will have an impact on the teaching efficacy of teachers. This study examines the effect of instructional leadership on the teaching self-efficacy of teachers by taking a sample of 147 teachers. Data analysis techniques using regression analysis. The results showed that instructional leadership had a significant effect on the teaching self-efficacy despite its low effect. As a recommendation, school principals as instructional leaders in improving teaching efficacy should not only be equipped with pedagogical knowledge, but must also be strengthened by knowledge school management capabilities..